An investigative discussion on the feasibility of an annual wealth tax in South Africa: are South African taxpayers ready for a wealth tax? - Mili, Simphiwe (Department of Finance and Tax, 2021)
In 2018 the Davis Tax Committee was tasked with the responsibility of investigating the feasibility of introducing an annual wealth tax in South Africa. This wealth tax would serve as a replacement for the existing wealth taxes that are Estate Duty, Donations Tax, Security Transfer Tax and Transfer Duty. There has since been great debate around this topic and the aim of this dissertation is to collate all the literature that has been researched on the wealth tax both nationally and internationally to conclude as to whether or not a wealth tax will be suitable for South Africa currently The two main reasons behind the proposal of a wealth tax are firstly, to increase tax contributions to the South African revenue. Secondly, it is as a measure of redress given that South Africa has great disparities in wealth with the wealth Gini coefficient currently reported to be 0.9. The wealth tax has not only been a contentious topic in South Africa, but has been debated globally. The OECD reported that initially 12 countries had implemented an annual wealth tax and now only 4 still have the tax operating in their economies. This dissertation focuses on lessons that can be learnt from international countries by conducting a country review on France, Germany and India. India is the only other BRICS country that had previously implemented the annual wealth tax and has since abolished it in 2015. Furthermore, it is important for the introduction of any tax in an economy to align with the principles of a good tax system. Adam Smith set out the canons of a good tax system such as simplicity, efficiency and equity and this dissertation assesses whether the wealth tax aligns with these ideals and investigates whether it would be fair to implement this tax as per the principles of vertical and horizontal equity. As mentioned above, South Africa already has existing wealth taxes. This study therefore interrogates whether the annual wealth tax is necessary since there are already wealth taxes that exist and whether these existing taxes on wealth meet the intended ideals of the wealth tax. There are advantages and disadvantages associated with the implementation of this tax. It was therefore important for this dissertation to juxtapose these. The dissertation concludes that the disadvantages outweigh the advantages of implementing a wealth tax in South Africa at the moment. The introduction of a wealth tax would therefore not be feasible in South Africa at the moment.